2008
DOI: 10.2215/cjn.05761207
|View full text |Cite
|
Sign up to set email alerts
|

Cilostazol Improves Long-Term Patency after Percutaneous Transluminal Angioplasty in Hemodialysis Patients with Peripheral Artery Disease

Abstract: Background and objectives: Peripheral artery disease (PAD) is common in patients on hemodialysis (HD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 35 publications
2
46
0
1
Order By: Relevance
“…Although adequately powered clinical trials on such medications in haemodialysis patients are still needed, it seems likely that intensive medical intervention might improve the prognosis in haemodialysis patients with diabetes mellitus and/or poor glycaemic control. Indeed, we have already reported the effectiveness of cilostazol in haemodialysis patients with PAD, although the data reported on were retrospective [30].…”
Section: Discussionmentioning
confidence: 99%
“…Although adequately powered clinical trials on such medications in haemodialysis patients are still needed, it seems likely that intensive medical intervention might improve the prognosis in haemodialysis patients with diabetes mellitus and/or poor glycaemic control. Indeed, we have already reported the effectiveness of cilostazol in haemodialysis patients with PAD, although the data reported on were retrospective [30].…”
Section: Discussionmentioning
confidence: 99%
“…31- 33 In patients with femoropopliteal disease who have undergone EVT, treatment with cilostazol is associated with a significant reduction of CD-TLR and in-stent restenosis, 34,35 as well as an improvement of long-term patency in dialysis patients after EVT. 36 Our study demonstrated a beneficial effect of cilostazol in reducing binary restenosis in dialysis patients after EVT, possibly because of the vasodilatory, antiinflammatory and antiproliferative effects on vascular smooth muscle cells. However, cilostazol administration did not appear to improve the CD-TLR-free rate in this study.…”
Section: Discussionmentioning
confidence: 51%
“…Several recent studies reported that cilostazol reduced restenosis and repeat revascularization after coronary intervention with either a bare-metal stent or a drug-eluting stent. 20,22,26,49,50 Similarly, cilostazol reduced restenosis after endovascular therapy in peripheral arteries, [15][16][17][18] and some studies reported the effectiveness of cilostazol in the prevention of restenosis after CAS. In 1 study, restenosis during a 29-month period after CAS occurred in none (0/ 27) of the patients who received cilostazol and in 15.7% (11/70) of patients who did not receive cilostazol.…”
Section: Discussionmentioning
confidence: 99%
“…14 In patients with coronary and peripheral artery disease, cilostazol has been shown to decrease restenosis and revascularization after catheter intervention. [15][16][17][18][19][20][21][22][23][24][25][26] Furthermore, some previous reports suggested that cilostazol reduced restenosis after CEA and CAS.…”
mentioning
confidence: 99%